ANALYSIS OF BALANCED SCORECARD APPLICATION FOR MEASURING PERFORMANCE OF CUSTOMER PERSPECTIVE, INTERNAL BUSINESS PERSPECTIVE, PERSPECTIVE LEARNING AND GROWTH IN PT. DAVICO ENGINEERING - Tomasoa, Erick Norman; Simanjuntak, Ramot P. (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
This study aims to Know how the application of BSC as a measurement tool at PT. Davico Engineering and to know how the company's performance if measured by customer perspective, internal business process perspective, learning and growth perspective.The data used comes from the company, interview and the spread of questionnaires to customers 35 respondents and employees as much as 35 respondents for the period of the last two years ie from 2015 - 2016. The research methodology used by the authors is the data analysis used in this study using three perspectives by developing relevant measurements using critical succes factors (CSFs) or by calculating the index of satisfaction. By the formula Ikmaks = R x PP Exmaks, Ikmin = R x PP x Exmin, Interval = (Ikmaks - Ikmin): 5. A conclusion that can be drawn from a customer perspective, internal business perspective, learning and growth perspective is satisfactory for each perspective in company performance. Keywords : Balanced scorecard, Measuring Performance, Balanced Scorecard Perspective.